Energy Efficiency in the Ceramic and Clay Building Materials Industry in Indonesia - Khusnul Ainia Aprilinda; Deni Kusumawardani (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The Indonesian clay and ceramic building materials industry is highly energy-intensive, yet firm-level evidence on energy efficiency during the 2010–2015 period remains limited. This study aims to measure energy efficiency and identify its key determinants within the sector. Energy efficiency is estimated using the Slack-Based Measure Data Envelopment Analysis (SBM-DEA), and a Tobit regression model is applied to examine firm-level determinants using data from the BPS Large and Medium Industry Survey (IBS). The results show an average efficiency score of 0.60, indicating a potential 40% improvement. Subsector disparities are evident, with sanitary ware and porcelain industries outperforming brick and tile industries. Tobit results show that business scale, firm status, and production composition have positive and significant effects on efficiency, while export orientation has a negative effect. These findings indicate that inefficiency is primarily driven by structural and firm-specific factors rather than technological constraints, implying that improving energy efficiency requires structural transformation alongside technological upgrading.